Structural Allograft Versus Synthetic Interbody Cage for Anterior Cervical Discectomy and Fusion: A Comparison of 1-Year Outcomes From a National Database. Issue 8 (October 2021) - Menon, Nandakumar; Turcotte, Justin; Patton, Chad
Study Design: Observational cohort study. Objective: To compare 1-year perioperative complications between structural allograft (SA) and synthetic cage (SC) for anterior cervical discectomy and fusion (ACDF) using a national database. Methods: The TriNetX Research Network was retrospectively queried. Patients undergoing initial single or multilevel ACDF surgery between October 1, 2015 and April 30, 2019 were propensity score matched based on age and comorbidities. The rates of 1-year revision ACDF surgery and reported diagnoses of pseudoarthrosis, surgical site infection (SSI), and dysphagia were compared between structural allograft and synthetic cage techniques. Results: A comparison of 1-year outcomes between propensity score matched cohorts was conducted on 3056 patients undergoing single-level ACDF and 3510 patients undergoing multilevel ACDF. In single-level ACDF patients, there was no difference in 1-year revision ACDF surgery ( P = .573), reported diagnoses of pseudoarthrosis ( P = .413), SSI ( P = .620), or dysphagia ( P = .529) between SA and SC groups. In multilevel ACDF patients, there was a higher rate of revision surgery (SA 3.8% vs SC 7.3%, odds ratio = 1.982, P < .001) in the SC group, and a higher rate of dysphagia in the SA group (SA 15.9% vs SC 12.9%). Conclusion: While the overall revision and complication rate for single-level ACDF remains low despite interbody graft selection, SC implant selection may result in higher rates of revision surgery in multilevel procedures despite yielding lower rates of dysphagia. Further prospective study is warranted.